Interactions familiales d'un enfant jumeau avec retard de langage oral : identification de situations facilitatrices pour l'enfant - Prevost Audrey; Caët, Stéphanie (My University, 2017)
The prevalence of speech and/or language delay in twins is higher than in singletons. Because of the specificity of the triadic situation in which twins acquire language, we wanted to analyze family interactions in order to identify situations that could facilitate the child's speech and be worked on in the context of a parental guidance. Video recordings were made at the home of one family of twins aged 6;2, in different situations: a family meal, a picture book reading, and a play time. Our analyses focused on one of the twins diagnosed with a speech and language delay. The child produced more and longer utterances in the picture book reading. This situation is also the situation where the rhythm of the interaction is slower, the child was most spoken to, with more open questions, and errors (in particular lexical errors) were almost all repaired by the adult (all repairs being in turn taken up by the child). The family meal is the situation where the child spoke the least and produced the shortest utterances; in this situation, although central in the child's everyday life and for his social and linguistic development, the child was rarely spoken to, questions were mostly closed, and errors less taken up.